2013
DOI: 10.1016/j.tsf.2013.03.124
|View full text |Cite
|
Sign up to set email alerts
|

Surface morphology, optical properties and conductivity changes of poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) by using additives

Abstract: The optical properties and electrical conductivity of highly conducting poly(3,4-ethylenedioxythiophene) (PEDOT) doped with poly(styrenesulfonate) (PSS) are reported as a function of the processing additive conditions. The addition of dimethyl sulfoxide (DMSO) increases the conductivity and modifies the dielectric response as observed from the ellipsometric studies. Also the surface roughness and morphology change with the composition of PEDOT:PSS:DMSO and film deposition conditions. The real part of the diele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 18 publications
4
74
1
Order By: Relevance
“…Significant enhancement in the conductivity of the PEDOT:PSS film was also observed by treating the film with drop of phenol, which exhibiting an enhanced film conductivity of 1054 S/cm. These conductivities are comparable with highest conductivities obtained after single treatment with other materials like ethylene glycol, DMSO and acids [35,44,45]. Actually both vapor and drop treatments should be done before annealing process because before annealing there is still some water in the film and hence polymer segments have more freedom to move.…”
Section: Resultssupporting
confidence: 76%
“…Significant enhancement in the conductivity of the PEDOT:PSS film was also observed by treating the film with drop of phenol, which exhibiting an enhanced film conductivity of 1054 S/cm. These conductivities are comparable with highest conductivities obtained after single treatment with other materials like ethylene glycol, DMSO and acids [35,44,45]. Actually both vapor and drop treatments should be done before annealing process because before annealing there is still some water in the film and hence polymer segments have more freedom to move.…”
Section: Resultssupporting
confidence: 76%
“…It is well known that the addition of solvents with high boiling points,s uch as DMSO,t oP EDOT:PSS drastically increases the conductivity of the films. [1,19,20] Thes ame effect is observed for PEDOT:PSTFSIK inks.F or PEDOT:PSTF-SIK, aD MSO concentration of 5wt% increases the film performance up to 80 times compared to the pristine ink, while higher concentrations of DMSO do not further improve the performance (see Figure S8 in the Supporting Information) and eventually cause the formation of inhomogeneities during film deposition.…”
Section: Angewandte Chemiementioning
confidence: 90%
“…PEDOT:PSS treated with LiCl metal salt has shown lower transmittance in the near infrared (NIRΨ region compared to the visible region; this could be related to the absorption of the PEDOT:PSS layer within this region. Gasiorowski and co-authors have reported that PEDOT:PSS layer has a small absorption coefficient in the UV and visible regions, while it has a higher absorption coefficient in the NIR region of the spectra [22].…”
Section: Optical Propertiesmentioning
confidence: 99%
“…The absorption band d has almost diminished and became as a shoulder on the latter peak. The absorption enhancement in the fully-treated device could be ascribed to the contribution of absorption of the salt-treated PEDOT:PSS layer within the complete device [22] and/or the light scattering and trapping within the complete device [23].…”
Section: Optical Propertiesmentioning
confidence: 99%